Hakikat Tujuan Pendidikan Islam - rina, khai (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
The aim of Islamic education is to create individuals who are obedient and submissive to Allah's commands, possess good intellectual abilities, have good character, are able to develop themselves, and are able to take an active role in advancing the lives of humanity. The purpose of Allah SWT in creating human beings and sending His prophets should be the foundation for the goals of Islamic education. In this regard, Islamic education should be directed towards efforts to realize the will of Allah SWT so that humans can achieve His satisfaction and follow the example of His prophets. Therefore, Islamic education should be aligned with the goals of Allah SWT in creating humans and providing guidance through His prophets. This research is a literature study that examines the nature of the goals of Islamic education. The literature review method includes indirect observation or looking at web platforms, internet, books, and other sources. Then, based on several expert opinions, which are presented in the form of notes, an analysis is conducted on relevant facts related to the predetermined topic. Goals are a standard of ability that can be identified and used as a guide in planning and directing efforts towards achieving other goals. Moreover, goals also serve as a limitation in decision-making, allowing us to focus on the objectives that we want to achieve.